Nursing Students’ Awareness and Occurrence of Needle Stick Injury (International Journal of Nursing Education, 2019)
Needle stick injuries caused by needles or sharps are one of the common accidental health hazards for the health care professionals. The present study is aimed to assess the awareness and occurrence of needle stick injuries among the nursing students. The research approach used was quantitative and the research design used was non experimental descriptive design to achieve the objectives of the study. The study participants were 134 students studying B.Sc Nursing in a selected college, Perinthalmanna. Structured questionnaire to assess the awareness regarding NSI and determine the occurrence of NSI was used to collect the data. The findings of the study indicate that majority of the students (61%) had inadequate awareness. Out of 134 nursing students, 44 students (33%) had experienced NSI; the most common device involved was the needle on the disposable syringe. The findings of the study indicate the need to enhance the awareness of the student nurses regarding NSI, safe practices, post exposure prophylaxis, protocols and guidelines of the institution, universal safety precautions and safe disposal of sharp items through educational interventions at their entry level of clinical practice.
Keywords: Needle stick injuries, Post exposure prophylaxis, Universal precautions, and Safe disposal of sharps